Mini-Arc for the Treatment of Female Stress Urinary Incontinence: Long-Term Prospective Evaluation by Patient Reported Outcomes. (20th January 2014) - Oliveira, Rui; Resende, Alexandre; Silva, Carlos; Dinis, Paulo; Cruz, Francisco
Abstract : Single-incision slings were introduced in the surgical treatment of female stress urinary incontinence (SUI) to lessen the morbidity associated with traditional midurethral slings. However, long-term reports on patient satisfaction are still scarce. This study describes the outcome of women treated with Mini-Arc at a mean follow-up of 45 months. In a previous report on 105 women with 15-month mean follow-up, 84 (80%) were found cured and 12 (11%) improved. Now, with a mean follow-up of 45 months, cured/improved patients were reassessed by telephone and completed Patient Global Impression of Improvement (PGI-I), Patient Global Impression of Severity (PGI-S), rated their improvement in a 0–100 scale, and answered if they would recommend the procedure. At 45-month follow-up, 73 women cured/improved were available for evaluation. Over 80% of the cured patients rated the improvement of SUI by the PGI-I as "very much better" or "much better, " reported their urinary tract condition to be "normal" on PGI-S, and described their improvement >70%. Ninety percent would recommend this procedure to a friend. The improved-patient population is very small( n = 7 ) . This study shows that the majority of patients cured/improved after Mini-Arc placement maintain a high degree of satisfaction at a long-term evaluation.